Slicing based on UML Diagram & Test Case Generation - Grover, Venus; Kumar, Jitender (International Journal of Computer Sciences and Engineering, 2019)
Software testing issued to evaluate a trait or potential of system and conclude that whether it meets necessary prospects. The most reasonably demanding part of testing is to plan of test cases. These days, UML has been broadly used for object oriented modeling and design. UML matamodel is used to describe structural and behavioural aspects of an architecture. However to recognize this performance is still hard, because the size of automatically generated model diagrams tends to be huge. To overcome this problem Software visualization model based slicing procedure has been developed. Model based slicing is a coherent advance to extract and recognize appropriate model parts or associated elements across diverse model views. On the basis of slicing criteria an original procedure has proposed to extort the sub- model from a big model diagrams. The planned methodology use the concept of model based slicing to slice the sequence diagram to extract the desired hunk. In the presented approach UML, conversion of UML into XML, Java DOM API for parsing and slicing has been used. Then Extracted Sequence Diagram has been generated by using the Editor. After that test case generation is performed.